2021
DOI: 10.3390/ijms222010994
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Allergic and Anti-Inflammatory Effects of Neferine on RBL-2H3 Cells

Abstract: Mast cells play a very important role in skin allergy and inflammation, including atopic dermatitis and psoriasis. In the past, it was found that neferine has anti-inflammatory and anti-aging effects on the skin, but its effect on mast cells has not yet been studied in detail. In this study, we used mast cells (RBL-2H3 cells) and mouse models to study the anti-allergic and inflammatory effects of neferine. First, we found that neferine inhibits the degranulation of mast cells and the expression of cytokines. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…Because of the RBL-2H3 cell line, an analogue of mast cells is suitable for studying the mechanisms of mast cell–mediated allergic reactions, and we used it to investigate the anti-allergy efficacy of Gt-EE [ 29 ]. First, the cytotoxicity of Gt-EE to RBL-2H3 cells was evaluated by a cell viability assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the RBL-2H3 cell line, an analogue of mast cells is suitable for studying the mechanisms of mast cell–mediated allergic reactions, and we used it to investigate the anti-allergy efficacy of Gt-EE [ 29 ]. First, the cytotoxicity of Gt-EE to RBL-2H3 cells was evaluated by a cell viability assay.…”
Section: Resultsmentioning
confidence: 99%
“…To research drugs with potential anti-allergic effects, the in vivo passive cutaneous anaphylaxis (PCA) model has been organized using anti-DNP IgE antibodies and antigens [ 29 ]. We induced topical and immediate hypersensitivity reactions in the ears of BALB/c mice and then monitored the quantity of Evans blue dye taken out from those ear tissues.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, we have researched and analyzed plant components with anti-inflammatory and antioxidant properties. Indeed, we found that they have very good anti-atopic dermatitis effects, such as neferine and cycloheterophyllin [ 29 , 30 , 31 ]. These research results can become the chemical structure basis for the development of effective drugs for the treatment of atopic dermatitis in the future.…”
Section: Discussionmentioning
confidence: 99%
“…First, the effect of α-boswellic acid on AD was assessed on DNBC-induced mice. DNBC-induced AD was developed according to a previously reported method [ 29 ]. The dorsal hairs of the mice were briefly shaved and then 100 μL and 20 μL of 1% DNCB in ethanol were applied to sensitive dorsal and ear skin for 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…Extracted from the seeds of lotus of Nymphaeaceae, neferine has antiarrhythmia, antihypertensive [ 133 ], antitumor [ 134 ], antiapoptotic, antioxidative, [ 135 ], anti-ischemic [ 136 ], antiallergic, and anti-inflammatory effects [ 137 ]. In terms of arrhythmia, by reducing the Na+, Ca2+ ion influx, and K+ outflow, nephrine can effectively prolong the Q-T interphase and slow down heart rate [ 138 ].…”
Section: Natural Products With Bioactivity In Afmentioning
confidence: 99%